Survival of extremely low birth weight infants at Charlotte Maxeke Johannesburg Academic Hospital - Kalimba, Edgar Mutebwa (My University, 2014)
Survival of extremely low birth weight (ELBW) infants in a resource limited public hospital setting is still low in South Africa. The study aimed at establishing the determinants of survival in this weight category of neonates who, due to limited intensive care facilities, were not mechanically ventilated.
DISSERTATION SUBMITTED IN PARTIAL FULFILLMENT OF REQUIREMENTS FOR A MASTER OF MEDICINE DEGREE IN PAEDIATRICS AND CHILD HEALTH (MMED PAED)
Keywords: Infant, Low Birth Weight--South Africa